Efficacy of two commonly available mouth rinses used as preprocedural rinses in children - Eapen Thomas (Wolters Kluwer Medknow Publications, 2011)
Aim: There are many studies on the effect of preprocedural mouth rinses in adults, but there is a dearth of the literature on the effects of these mouth rinses in children. This study aims to evaluate the efficacy of two commercially available brands, one containing chlorhexidine 0.12% (Colgate Periogard) and the other containing cetylpyridinium chloride 0.05% (Johnson and Johnson's Reach) used as preprocedural mouth rinses in children. Materials and Methods: The study was conducted on 18 patients in the age group of 10-15 years. A crossover design was used with the random assignment of the first rinse tested and a wash out period of at least 1 week before the second rinse was used. The saliva samples were collected prerinse, 2 min, 30 min, and 60 min after rinsing with the solution. The samples were inoculated and cultured for aerobic and anaerobic microorganisms. After 48 h, the resultant bacterial colonies were counted. Results: Statistical analysis was done using Wilcoxon's signed rank test, ANOVA, and Newman-Keul's studentized range test. Periogard had the highest percentage reduction in both aerobic and anaerobic microorganisms followed by Reach and the least effective was normal saline which was used as a control. Conclusions: Periogard is comparatively better as a preprocedural mouth rinse than Reach.